Condensation corrosion of carbon steel at low to moderate surface temperature and iron carbonate precipitation kinetics - Islam, M.; Pojtanabuntoeng, T.; Gubner, Rolf (Elsevier, 2016)
© 2016 Elsevier Ltd. This study investigates the influence of surface temperature and droplet retention time (DRT) on the corrosion rate, FeCO3 supersaturation, and scaling tendency of carbon steel exposed to water condensation. This corrosion phenomenon is also known as top of the line corrosion (TLC). TLC is found to be governed by surface temperature irrespective of water condensation rates (WCR) at low surface temperature (15°C). The results also demonstrate that the DRT directly influences FeCO3 supersaturation and scale formation. A new kinetic constant for the calculation of FeCO3 precipitation rate under condensing condition at the top of the line is proposed.